Experiment on Fracturability of Shale Reservoir in Yingxiongling Area, Qinghai Oilfield - Chen, Xiwen; Li, Bin; Yu, Fusheng (Scientific Journal of Technology, 2026)
The Yingxiongling Area of Qinghai Oilfield is rich in shale oil resources; however, there are still gaps in the analysis of reservoir geological characteristics and the fracturability evaluation system in this region. To address this, a fracturability evaluation model was established through systematic experiments on reservoir engineering geological characteristics, with the results as follows: The reservoir in the Upper Member of Ganchaigou Formation is prominently characterized by interbedded sedimentation of calcareous shale and calcitic dolomite, with an average porosity of 5.7%. The pore size is concentrated in the micron-scale range of 0.001 0.1 μm, and micron-scale pores are well-developed. The mineral composition is dominated by dolomite, calcite, and clay minerals, among which the average content of clay minerals reaches 65%, and the average rock mechanical brittleness index is 41.76%. Natural fractures in the reservoir are poorly developed, and the difference in fracture pressure between limestone intervals and shale intervals is 10.78 16.68 MPa, which is unfavorable for vertical fracture propagation. The shale reservoir fracturability model shows that the average fracturability index is 0.34, indicating low fracturability and difficulty in forming a complex fracture network. Based on the fracturability model and geological characteristics, a reservoir reconstruction mode of "three-dimensional horizontal well pattern + zipper-type volume fracturing" is proposed. By adopting the technologies of close spacing fracturing + limited-entry perforation + large-displacement continuous sanding, the complexity of fractures is further improved to achieve net pressure interlayer breakthrough.